Konseling Kelompok Sebagai Dasar Untuk Mereduksi Kesulitan Belajar Siswa - Hijr Amelya; Isabelle Clara; Muhammad Ridho Bima Addli; Nabila Azzahra; Ratna Sari Dewi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Education plays a crucial role in shaping students' futures; however, many students face various learning barriers. These obstacles may include substances that affect motivation and concentration, emotional stress, and social challenges that hinder understanding. One effective solution to address these issues is group counseling. Group counseling allows students to interact with their peers, fostering an environment of shared experiences and mutual support. This process can enhance students' self-confidence, social skills, and reduce psychological stress. This study aims to examine the benefits of group counseling in overcoming students' learning difficulties and to identify challenges in its implementation. The research employs a literature review method by analyzing various relevant sources on the topic. The findings indicate that group counseling has a positive impact on students’ academic and emotional development. Students who participate in group counseling tend to demonstrate improved learning motivation, communication skills, and better self and social awareness. These findings are expected to make a meaningful contribution to the development of more effective school counseling services, with an emphasis on integrating social and local cultural factors. Furthermore, the results of this study can support education policymakers and educators in designing interventions that are more responsive to students’ needs in the learning environment.